2017
DOI: 10.1097/gox.0000000000001588
|View full text |Cite
|
Sign up to set email alerts
|

Examining Length of Hospital Stay after Microsurgical Breast Reconstruction: Evaluation in a Case-Control Study

Abstract: Background:While possessing numerous benefits, microsurgical breast reconstruction is associated with longer operative times and post-operative hospital length of stay compared to implant-based reconstruction. We therefore evaluate factors associated with increased length of stay (LOS) after microsurgical breast reconstruction with a case-control study design.Methods:All patients undergoing immediate or delayed abdominally-based microsurgical breast reconstruction over a two-year time period were identified. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Bilateral reconstructions had statistically and clinically significantly longer lengths of stay by 2.4 days ( Table 2). This increase for bilateral procedures is well documented in the literature [15]. It is also expected as bilateral surgery is more invasive, lasts longer and is associated with a longer recovery in terms of mobilization.…”
Section: Table 4 Regression Model Of Total Morphine Use For Patientsmentioning
confidence: 63%
See 1 more Smart Citation
“…Bilateral reconstructions had statistically and clinically significantly longer lengths of stay by 2.4 days ( Table 2). This increase for bilateral procedures is well documented in the literature [15]. It is also expected as bilateral surgery is more invasive, lasts longer and is associated with a longer recovery in terms of mobilization.…”
Section: Table 4 Regression Model Of Total Morphine Use For Patientsmentioning
confidence: 63%
“…Our length of stay is however similar to representative UK cohorts of DIEP and other autologous tissue-based breast reconstructions which have reported mean length of stay ranging between 6.8 and 10.2 days [ 16 - 18 ]. Historically earlier discharges have been reported in North American studies with mean length of stay between 4 and 5 days [ 14 , 15 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received ciNPT were required to remain an inpatient for at least 5–7 days for nursing care until the Prevena dressing was removed, precluding this measure from being clinically relevant when measuring wound complication outcomes. Patients with comorbidities such as diabetes may require increased length of stay to optimize glycaemic management pre- and post-surgery [ 19 , 20 , 21 ]. In addition, obesity has been linked to an increased length of stay with longer observation periods often due to a prolonged, more complex postoperative recovery [ 18 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with comorbidities such as diabetes may require increased length of stay to optimize glycaemic management pre- and post-surgery [ 19 , 20 , 21 ]. In addition, obesity has been linked to an increased length of stay with longer observation periods often due to a prolonged, more complex postoperative recovery [ 18 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] The literature also shows that transversus abdominis plane (TAP) blocks reduce the level of narcotics that patients require to control their pain after abdominally based breast reconstruction. 18,19 Goals of DIEP flap postoperative protocols include enhanced patient outcomes, improved pain control with minimizing narcotics, and controlling costs with decreasing LOS. Previous investigators in other fields have shown that patient expectations of hospital stay after surgery may affect inpatient stay after surgery.…”
mentioning
confidence: 99%